1993
DOI: 10.1159/000204383
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia: Recovery from in vitro Oxidative Stress

Abstract: Red blood cells in iron deficiency anemia (IDA) have a decreased activity of essential antioxidant enzymes. The present study examined the effect of in vitro exposure to oxidative agents in IDA cells and their recovery capacity. Red cells of 26 IDA patients and 10 healthy subjects were examined. Cells of IDA patients had higher levels of reduced glutathione (GSH), and normal methemoglobin and malonyldialdehyde (MDA) levels. Exposure to butyl hydro-peroxide revealed a dose-dependent sensitivity in IDA cells, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 9 publications
(10 reference statements)
1
19
0
Order By: Relevance
“…In the literature (9,14,19), microcytic red blood cells had higher susceptibility to oxidant and high malonyldialdehyde production. Similarly, our results indicated that blood ROS concentrations were higher in patients with IDA than controls.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature (9,14,19), microcytic red blood cells had higher susceptibility to oxidant and high malonyldialdehyde production. Similarly, our results indicated that blood ROS concentrations were higher in patients with IDA than controls.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of studies on oxidative stress in IDA are based on lipid peroxidation measurements, and their results are contradictory. It has been determined that red blood cell susceptibility to in vitro oxidation is increased in IDA patients [4,32]; however, some authors have suggested that there is no evidence of increased susceptibility of red blood cells to lipid peroxidation [1,23]. Biomolecular targets of free radicals extend beyond lipids, and DNA oxidation may have more severe consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Iodoacetamide inhibits GSHPX by reacting with GSH and inhibits perroxiredoxin by reacting with the protein thiol groups [35]. Interestingly, a decrease in GSHPX activity has been reported in iron deficiency anemic patients and experimentally induced iron deficiency anemic rabbits [5,13,16,18]. With a reduction of GSHPX activity, there is an increase in the hydrogen peroxide generated at the surface of the membrane that is not neutralized.…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress during anemia is supported by increased lipid peroxidation [5,7,13–17], a decrease in antioxidant defense enzymes including glutathione peroxidase [5,13,16] and a greater susceptibility to the addition of pro-oxidants [18,19]. The presence of oxidative stress in RBCs during anemia has, however, not been consistently observed [20,21].…”
Section: Introductionmentioning
confidence: 99%